The antimicrobial peptide Magainin-2 interacts with BamA impairing folding of E. coli membrane proteins - Di Somma, Angela; Cané, Carolina; Moretta, Antonio; Illiano, Anna; Pinto, Gabriella; Cavasso, Domenico; Amoresano, Angela; Paduano, Luigi; Duilio, Angela (Frontiers in Chemistry, 2022)
Antimicrobial peptides (AMPs) are a unique and diverse group of molecules endowed with a broad spectrum of antibiotics properties that are being considered as new alternative therapeutic agents. Most of these peptides are membrane-active molecules, killing bacteria by membrane disruption. However, recently an increasing number of AMPs was shown to enter bacterial cells and target intracellular processes fundamental for bacterial life. In this paper we investigated the mechanism of action of Maganin-2 (Mag-2), a well-known antimicrobial peptide isolated from the African clawed frog Xenopus laevis, by functional proteomic approaches. Several proteins belonging to E. coli macromolecular membrane complexes were identified as Mag-2 putative interactors. Among these, we focused our attention on BamA a membrane protein belonging to the BAM complex responsible for the folding and insertion of nascent β-barrel Outer Membrane Proteins (OMPs) in the outer membrane. In silico predictions by molecular modelling, in vitro fluorescence binding and Light Scattering experiments carried out using a recombinant form of BamA confirmed the formation of a stable Mag-2/BamA complex and indicated a high affinity of the peptide for BamA. Functional implications of this interactions were investigated by two alternative and complementary approaches. The amount of outer membrane proteins OmpA and OmpF produced in E. coli following Mag-2 incubation were evaluated by both western blot analysis and quantitative tandem mass spectrometry in Multiple Reaction Monitoring scan mode. In both experiments a gradual decrease in outer membrane proteins production with time was observed as a consequence of Mag-2 treatment. These results suggested BamA as a possible good target for the rational design of new antibiotics since this protein is responsible for a crucial biological event of bacterial life and is absent in humans.